Imiona chrześcijańskie w Synodyku nowogrodzkim z końca XIV–XV wieku - Wójtowicz, Marian (Studia Rossica Posnaniensia, 2021)
The article contains an analysis of Christian names selected from the oldest synodicon written in the Lisitsky monastery near Veliky Novgorod. The analysis comprises 3190 names of lay people, amongst which are 208 male names and 58 female names. The author discusses the group of given names (basic forms, their phonetic, morphological variants and frequency, as well as rarely used names that occurred in the synodicon).